Dividend growth predictability and the price-dividend ratio - Piatti, I; Trojani, F (INFORMS, 2019)
Asymptotic tests over-reject the null of no predictability in present-value models. We develop a nonparametric testing approach in state space models, implying reliable finite sample inference under weak assumptions on price-dividend ratio and dividend shocks. We find sharp evidence of return predictability in postwar US data, but a less consistent evidence of dividend predictability, which is significant only using cash-flow proxies reflecting information from mergers and acquisitions. These findings reconcile the diverging conclusions of present-value models and common predictive regressions, in a way that is robust to the choice of the predictive variables, the sample period and alternative cash-flow proxies.